Extraction and characterization of lipase from seed of arachis hypogaea l / Siti Nor Zulaiha Zakariya - Zakariya, Siti Nor Zulaiha (Faculty of Applied Sciences, 2017)
Production cost of microbial lipase enzyme is high and industrial scale is still limited due to high production costs. Seeds are commonly productive in triacylglycerols, which act as compact source of energy for the fresh nascent plant. Therefore, seed lipase from Arachis hypogaea L was introduced as biocatalyst due to low cost. Germinated and ungerminated Arachis hypogaea L. seeds is use to determine the enzyme activity and selectivity by using a mix substrate (coconut oil and cooking oil). Base-methylation and acid methylation process were used to convert the free fatty acid (FFA) to fatty acid methyl ester before analyze with gas chromatography (GC-MS). Particularly, the eight dominant fatty acids in both seed show a change in percent of fatty acids after hydrolyze and it prove that the enzyme in the both seeds are selective. Both of the seeds shows that their enzyme selectivity is more toward oleic acid which have high percent change after hydrolyze. Fatty acid shows the highest percentage in germinate seed compare to ungerminated seed. Enzyme activity of peanut seed lipase show that the lipase more active in germinate seed compare to ungerminated seed. Germinate seed lipase shows a great enzyme activity because rate controlling of lipase in the middle of germination and the activity of the lipase is great during that time.